Evaluating a low‐intensity cognitive behavioural program for young people in regional Australia. (10th May 2020) - Fox, Rachael; Nic Giolla Easpaig, Brona; Roberts, Russell; Greig, Jenni; Burmeister, Oliver; Dufty, Janelle; Thomas, Shane
Abstract: NewAccess is a low‐intensity cognitive behavioural program which was recently trialled for the first time in Australia for clients aged under 18. Given that accessing support earlier tends to result in better outcomes for people with mild‐to‐moderate mental health issues, having NewAccess available for young people has the potential to reduce the likelihood of mild‐to‐moderate mental health concerns developing into more serious, or chronic mental illness over time for some clients, while also freeing up resources for those with more severe support needs. This mixed methods approach presents the findings of an independent evaluation of the program delivered out of two regional headspace centres in 2017‐2019. From an initial sample of 165 young participants aged between 12 and 25, 109 completed the program. Of those who completed the program 60 were under the age of 18. The standardised assessment and outcome measures indicated a very good response to the program, with the majority showing significant improvements in their depression, anxiety and psychological distress scores. The overall 'reliable improvement' and 'recovery rates' were 64.2% and 72.3% respectively. Overall, the results indicated this program was an acceptable and efficacious intervention for young people in rural settings, when delivered in a 'youth‐friendly' service environment.